Double cusp encounter by Cluster: double cusp or motion of the cusp? - C. P. Escoubet; J. Berchem; K. J. Trattner; F. Pitout; F. Pitout; R. Richard; M. G. G. T. Taylor; J. Soucek; B. Grison; H. Laakso; A. Masson; M. Dunlop; et al. (Annales Geophysicae, 2013)
Modelling plasma entry in the polar cusp has been successful in reproducing ion dispersions observed in the cusp at low and mid-altitudes. The use of a realistic convection pattern, when the IMF-By is large and stable, allowed Wing et al. (2001) to predict double cusp signatures that were subsequently observed by the DMSP spacecraft. In this paper we present a cusp crossing where two cusp populations are observed, separated by a gap around 1° Invariant Latitude (ILAT) wide. Cluster 1 (C1) and Cluster 2 (C2) observed these two cusp populations with a time delay of 3 min, and about 15 and 42 min later Cluster 4 (C4) and Cluster 3 (C3) observed, respectively, a single cusp population. A peculiarity of this event is the fact that the second cusp population seen on C1 and C2 was observed at the same time as the first cusp population on C4. This would tend to suggest that the two cusp populations had spatial features similar to the double cusp. Due to the nested crossing of C1 and C2 through the gap between the two cusp populations, C2 being first to leave the cusp and last to re-enter it, these observations are difficult to be explained by two distinct cusps with a gap in between. However, since we observe the cusp in a narrow area of local time post-noon, a second cusp may have been present in the pre-noon sector but could not be observed. On the other hand, these observations are in agreement with a motion of the cusp first dawnward and then back duskward due to the effect of the IMF-By component.